2018
DOI: 10.1007/s10015-018-0462-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kampo disease states using facial images

Abstract: In the traditional Japanese (Kampo) medicine, diagnosis is based on the observation of facial color and expression. Disease states that are diagnosable from facial characteristics include blood stagnation, blood deficiency, and yin deficiency. However, these diagnoses are subjective and require lots of experience. In this paper, we aimed to quantify facial diagnosis by creating a system to evaluate the severity of disease states using feature values obtained from facial images. A Kampo physician evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Our previous studies demonstrated that tongue color reflects the diagnosis in Kampo medicine [ 19 ], and evaluation of Kampo Disease State is possible with images of the face and tongue [ 20 , 21 ]. Facial color diagnosis is also an important diagnostic method in Kampo medicine and traditional Chinese medicine (TCM).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that tongue color reflects the diagnosis in Kampo medicine [ 19 ], and evaluation of Kampo Disease State is possible with images of the face and tongue [ 20 , 21 ]. Facial color diagnosis is also an important diagnostic method in Kampo medicine and traditional Chinese medicine (TCM).…”
Section: Discussionmentioning
confidence: 99%
“…As in Matsushita et al [6], after each of the four Kampo doctors made a diagnosis, machine learning was performed using each evaluation as the ground truth. In this study, it was found that individual differences were generated among doctors in their evaluation of tongue images.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists diseases that can be diagnosed based on an inspection of the face and tongue of the patient using Kampo medicine. To computerize descriptive diagnosis, Matsushita et al [6] proposed a method to assess diseases of Kampo medicine using the facial images of patients. Blood deficiency, blood stagnation, and yin deficiency can be diagnosed using facial images.…”
Section: Introductionmentioning
confidence: 99%